DFID’s approach to delivering impact - ICAI (Independent Commission for Aid Impact (ICAI), 2015)
UK aid, at its best, makes a real and positive difference to the lives and livelihoods of poor people around the world. Ensuring the best po ssible performance across a large and multifaceted aid programme is, h owever, a complex management challenge. This report reviews ICAI’s pre vious 44 reports and looks at how well DFID ensures positive, long-ter m, transformative impact across its work.